HUKUM PERSAINGAN USAHA (Peran KPPU Teori dan Praktek di Indonesia) - Herniati (The Juris, 2018)
The business world is a world that cannot stand alone. A country will develop if the business world runs and develops. A business world that is growing rapidly and advancing without being regulated by clear signs and rules will not be profitable in the end. Many aspects of various other worlds are involved both directly and indirectly with this business world. Such linkages sometimes do not give priority to the business world, which in the end makes the business world must submit and follow the existing signs and often even prioritize the business world so that it ignores the existing rules. Monopolistic Practices and unfair business competition in Indonesia occur from large businesses controlling business practices from upstream to downstream. Law Number 5 Year 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, is expected to be able to bind the government to be more objective and professional in regulating the business world in Indonesia. The presence of Law Number 5 of 1999 as a means of social control, namely trying to safeguard the public interest and prevent monopolistic practices and/or unfair business competition, creates a conducive business climate through regulating fair business competition and trying to create effectiveness and efficiency in business activities. The duty of the KPPU is to supervise the implementation of the Law, with supervision that it is expected that business actors can compete in a healthy manner so that all economic activities can run more efficiently and benefit consumers widely. KPPU has the authority, among others: to receive reports from the public and or from business actors about allegations of monopolistic practices and or unfair business competition; conduct research on allegations of business activities or actions of business actors that can lead to monopolistic practices and unfair business competition. In examining cases of alleged monopoly and unfair business competition KPPU is also authorized to impose administrative sanctions on business actors who violate the Anti-Monopoly Law.